Sustainable Development Goals in Corporate Reporting: Analysis of Economic, Social, and Environmental Disclosure (Survey among Public Listed Companies in Indonesia) - Megawati, Lokita Rizky; Pratama, Arie (International Journal of Energy Economics and Policy, 2024)
This research purpose was to describe the disclosure of the Sustainability Development Goals (SDG) in Indonesian companies’ corporate reporting to further analyse sustainability issues. This study employed a descriptive, quantitative method. This research collected data from 443 Indonesian publicly listed companies divided into nine types of industries. This study classified 17 SDG targets into three sustainability-related performance indicators: Economic, Social, and Environmental. The data were analysed using descriptive statistics, Analysis of Variance , and cluster analysis. This research found that: (1) the disclosure of the SDG items in corporate reporting is still low at 38%; (2) SDG disclosure made by the company still focused more on the economic theme of sustainability, rather than environmental or social; (3) there are significant differences among industries in terms of economic disclosure, but there are no differences in terms of environmental and social disclosure; (4) there are five clusters formed by the cluster analysis, and the general cluster descriptions indicate that only 15% of the companies have good disclosure quality in terms of Economic, Social and Environmental issues, and around 24% of the companies still have no or few disclosures of sustainability-related issues. This implies that Indonesian companies still face a significant challenge in promoting corporate reporting to satisfy investors’ need for sustainability.